Effects of solvent on structures and properties of electrospun poly(ethylene oxide) nanofibers. Issue 5 (28th September 2017) - Song, Zhe; Chiang, Sum Wai; Chu, Xiaodong; Du, Hongda; Li, Jia; Gan, Lin; Xu, Chengjun; Yao, Youwei; He, Yanbing; Li, Baohua; Kang, Feiyu
ABSTRACT: Poly(ethylene oxide) (PEO) nanofibers were prepared by electrospinning PEO solution with a mixed solvent of ethanol and deionized water. The results show that the mixed solvent system has noteworthy influences on structures and properties of electrospun PEO nanofibers, including molecular chain orientation, crystallinity degree, surface morphology, fiber diameter, diameter distribution, spinnability, and productivity. With increasing ethanol content in the mixed solvent, wrinkly morphologies appear on the surface of PEO nanofibers due to a high evaporation rate of ethanol during electrospinning process. The dielectric constant, dipole moment, conductivity, density, boiling point, and solubility parameter of the mixed solvent become lower with the ethanol content increasing. Besides, the hydrogen‐bonding interactions between PEO and solvents become weaker. As a result, PEO nanofibers with larger diameters, lower molecular chain orientation, and crystallinity degree are obtained. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45787. Abstract :